Disqualification of the Candidate Pair for the Elected Regional Head of Sabu Raijua Regency - Irfan Amir (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2021)
The dispute over the results of the regional head election of Sabu Raijua Regency which is legally formal has passed the deadline for submitting a dispute request (expired). Through the Constitutional Court Decision No. 135/PHP.BUP-XIX/2021, cancels KPU's decision regarding the determination of the elected pairs of candidates for Regent and Deputy Regent and orders a re-election and disqualification of the elected candidate pair. This research is normative juridical research (doctrinal law research) using a statutory approach and a case approach. The data obtained were analyzed and presented descriptively analytically. The finding in this study indicates that, the basis for the consideration of the Constitutional Court in ordering a re-election and disqualifying the chosen pair chosen by the people of Sabu Raijua Regency, is based on the legal fact that the violation of the principle of 'honest' from the Orient Patriot Riwu Kore pair who from the beginning of the registration stage the prospective candidate pair hides the United States citizenship status he holds, which if this foreign citizenship status is known from the beginning, then administratively does not qualify as a candidate pair. In addition, the election dispute for Sabu Raijua Regency is specific and casuistic which creates a legal need and vacuum, and if it is not acted upon, in principle it has violated the exclusive rights of citizens in government guaranteed by the 1945 Constitution.